2018
DOI: 10.3390/agriculture8050068
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Variability of Floral and Agronomic Characteristics of Newly-Bred Cytoplasmic Male Sterile Rice

Abstract: Male sterility enabled commercialization of heterosis in rice but low seed set remains a constraint on hybrid dissemination. We evaluated 216 F 6 maintainer lines for agronomic and floral characteristics in augmented design and selected 15 maintainer lines, which were testcrossed with IR58025A. Five backcrosses were conducted to transfer cytoplasmic male sterility (CMS) to select maintainer lines. Newly-bred BC 5:6 CMS lines were evaluated for outcrossing rates and agronomic characteristics. There were highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…To enhance the efficiency of seed set in (CMS) lines, it is required to study the stigma length and stigma width traits because large stigma size facilitates out crossing rate during hybrid seed production (El-Namaky, 2018). The results revealed that, stigma length of G46A did not vary significantly and it was 1.41 and 1.50 mm for 2015 and 2016 seasons, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To enhance the efficiency of seed set in (CMS) lines, it is required to study the stigma length and stigma width traits because large stigma size facilitates out crossing rate during hybrid seed production (El-Namaky, 2018). The results revealed that, stigma length of G46A did not vary significantly and it was 1.41 and 1.50 mm for 2015 and 2016 seasons, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Narrow cytoplasmic genetic diversity observed both in rice hybrids and varieties has led breeders to look for new cytoplasmic resources and to characterize their effects on traits of agronomic value (Huang et al, 2013;Kumar et al, 2013;Toriyama and Kazama, 2016;El-Namaky, 2018). In order to study the effects of cytoplasm, nucleus, and interaction between nucleus and cytoplasm on agronomic traits in rice, Tao et al (2004) evaluated fifteen isolines obtained by crossing five widely used japonica cytoplasm resources as females by three distinct japonica rice cultivars followed by several backcrosses to the male recurrent parent.…”
Section: Ricementioning
confidence: 99%
“…The CMS female lines are crossed by appropriate fertile restorers and produce hybrid seeds in self-pollinating crop species like rice. Accordingly, the CMS system provides a valuable approach for commercial exploitation of hybrid technology and producing high-yielding hybrid rice ( El-Namaky, 2018 , Liao et al, 2021 ). The hybrid rice based on the CMS framework has prompted an increment of grain yield by over 20% compared with the conventional rice cultivars ( Abebrese et al, 2018 , Toriyama et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale hybrid rice is limited due to its low capacity of hybrid seed production and high seed cost. To cope with these constraints, it is essential to enhance the outcrossing ability of CMS lines ( El-Namaky, 2018 ). The outcrossing of CMS lines is greatly increased by improved floral traits such as; longer duration of floret opening, wider angle of floret opening, longer stigma, and higher stigma exsertion ( Anis et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation